badge image

Enroll For Free Now & Improve Your Performance.

×
User Icon
User Icon
User Icon
User Icon
User Icon

Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
Grade: 11

                        

if sinA +sin^2 A = 1 then prove that cos ^8 A + 2cos^6 A + cos ^4 A=1

3 years ago

Answers : (3)

Arun
24742 Points
							
We can also prove that
cos^8A + 2 cos^6A + cos^4A - 1 = 0
Hence
sinA+sin^2A=1
=>sinA=1-sin^2A=cos^2A
Now
cos^12A+3cos^10A+3cos^8A+cos^6A-1
Using cos^2A=sinA in this expression we get
sin^6A+cos^6A+3cos^10A+3cos^8A-1
=1-3sin^2Acos^2A+3cos^10A+3cos^8A-1
=-3sin^2Acos^2A+3cos^10A+3cos^8A
=-3sin^2Acos^2A+3sin^4A+3cos^10A
=3sin^2A(sin^2A-cos^2A)+3cos^10A
=-3sin^2Acos2A+3cos^10A
=-3sin^2Acos2A+3cos^4Acos^6A
=-3sin^2Acos2A+3sin^2Acos^6A
=3sin^2A(cos^6A-cos2A)
=3sin^2A(sin^2Acos^2A-cos2A)
=3sin^2A(cos^2Asin^2A-cos^2A+sin^2A)
=3sin^2A{cos^2A(sin^2A-1)+sin^2A}
=3sin^2A{-sinAcos^2A+sin^2A}
=3sin^2A{-sinAsinA+sin^2A}
=3sin^2A{=sin^2A+sin^2A}
=0
3 years ago
shaunak
19 Points
							
sinA+sin^2A=1
=>sinA=1-sin^2A=cos^2A
Now
cos^12A + 3cos^10A + 3cos^8A + cos^6A-1
Using cos^2A = sinA in this expression we get
sin^6A + cos^6A + 3cos^10A + 3cos^8A-1
=1 - 3sin^2 Acos^2A + 3cos^10A + 3cos^8A-1
=-3sin^2A cos^2A + 3cos^10A + 3cos^8A
=-3sin^2A cos^2A + 3sin^4A + 3cos^10A
=3sin^2A (sin^2A-cos^2A) + 3cos^10A
=-3sin^2A cos2A + 3cos^10A
=-3sin^2A cos2A + 3cos^4A cos^6A
=-3sin^2A cos2A + 3sin^2A cos^6A
=3sin^2A (cos^6A-cos2A)
=3sin^2A (sin^2A cos^2A - cos2A)
=3sin^2A (cos^2A sin^2A - cos^2A + sin^2A)
=3sin^2A {cos^2A (sin^2A-1) + sin^2A}
=3sin^2A {-sinA cos^2A + sin^2A}
=3sin^2A {-sinA sinA + sin^2A}
=3sin^2A {-sin^2A + sin^2A}
=0
2 years ago
Nikhileshsing Kailassing Rajput
11 Points
							As, sina+sin^2a=1So, sina=cos^2aAs, cos^8a+2cos^6a+cos^4=sin^4a+2sin^2.cos^2a+cos^4a=(sin^2a+cos^2a)^2
						
2 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies


Course Features

  • 731 Video Lectures
  • Revision Notes
  • Previous Year Papers
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Test paper with Video Solution


Course Features

  • 31 Video Lectures
  • Revision Notes
  • Test paper with Video Solution
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Previous Year Exam Questions


Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details